Admirative Category with an Assessment of Possibility and Motivation in Russian and Persian Interrogative Sentences - T. Kh. Kahnamouei; A. A. Hosseini (Вестник Кемеровского государственного университета, 2022)
In Russian and Persian, the category of indirect evidentiality points out to some unreliable source of information. The category of admirativity expresses unexpected and new information gained by the speaker. Such interrogative sentences convey combine admirativity with diff erent modal meanings. Foreign students of Russian often fi nd it hard to distinguish these meanings in Russian interrogative sentences. The authors compared Russian and Persian interrogative sentences and the linguistics tools that refl ect the admirative category with an assessment of modal meanings of possibility and motivation. This is the fi rst research of the category of admirativity in the Persian language and the fi rst publication on the comparison of Russian and Persian interrogative sentences, as well as on the relationship between admirativity and modal meanings in Russian and Persian interrogative sentences. The research objective was to perform a comparative analysis of admirativity in Russian and Persian interrogative sentences and to study the situations in which this meaning conveys the surprise of the speaker from the availability or lack of possibility to perform a certain action. In both languages, admirativity can accompany the feeling of motivation in the subject of the speech act. The findings can be useful in teaching Russian as a foreign language.